Spinal Tuberculosis: A Literature Review. Issue 1 (January 2019) - Ali, Ahmed; Musbahi, Omar; White, Veronica L.C.; Montgomery, Alexander Sheriff
Abstract : Spinal tuberculosis (STB) is a common form of extrapulmonary tuberculosis (TB), accounting for 3.7% of TB cases in the United States. The most common presentation is chronic back pain, for which the diagnosis of STB can be easily overlooked, leading to the development of neurological deficits and osseous deformities of the spine. The risk of TB is increasing as a result of multidrug-resistant TB strains. The first line of treatment is antitubercular medical therapy, with surgical intervention being indicated for decompression of neurological elements that have been unresponsive to medical therapy, the restoration of spinal stability, and the correction of deformity. Early diagnosis and treatment improve the prognosis. This review of the current literature on STB offers an insight into our experience on STB treatment at a western STB specialist hospital.